2005
DOI: 10.1111/j.1365-294x.2005.02764.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative influence of natural selection and geography on gene flow in guppies

Abstract: Two general processes may influence gene flow among populations. One involves divergent selection, wherein the maladaptation of immigrants and hybrids impedes gene flow between ecological environments (i.e. ecological speciation). The other involves geographic features that limit dispersal. We determined the relative influence of these two processes in natural populations of Trinidadian guppies (Poecilia reticulata). If selection is important, gene flow should be reduced between different selective environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
378
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(409 citation statements)
references
References 131 publications
(198 reference statements)
15
378
4
Order By: Relevance
“…Fish that are displaced from the UN during seasonal flood events may be prevented from returning upstream by barriers to gene flow such as waterfalls (Crispo et al 2006, van Oosterhout et al 2007a. Compensatory upstream migration in the lowlands may allow the return of displaced fish that have not been swept over such barriers (see Barson et al 2009, Willing et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fish that are displaced from the UN during seasonal flood events may be prevented from returning upstream by barriers to gene flow such as waterfalls (Crispo et al 2006, van Oosterhout et al 2007a. Compensatory upstream migration in the lowlands may allow the return of displaced fish that have not been swept over such barriers (see Barson et al 2009, Willing et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Gene flow can be restricted in such situations either by selection against dispersers moving between populations in different habitats or by individual preference for remaining in a particular habitat (Nosil, 2004; Nosil, Vines, & Funk, 2005). This is usually manifested by an association between phenotypic differences and environmental differences (IbE, Crispo, Bentzen, Reznick, Kinnison, & Hendry, 2006; Nosil, 2012; Rundle & Nosil, 2005; Shafer & Wolf, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the Oropouche drainage likely had confluences with a different drainage system on mainland South America and would have been exposed to different colonizing events. Second, a study has provided a detailed analysis of populations from within a single river system, the Marianne (Crispo et al, 2006). This study revealed considerable differentiation among sites within the river and attributed the differentiation to waterfall barriers and isolation by distance.…”
Section: Introductionmentioning
confidence: 99%
“…The second involves adaptive divergence under variable selection pressures whereby dispersers or hybrids tend to have lower fitness than residents and gene flow between ecological environments can thus be impeded (Lu and Bernatchez, 1999;Ogden and Thorpe, 2002;Rundle, 2002;reviewed by Schluter, 2000;Hendry, 2004). Yet, assessing the contribution of these various processes to intraspecific genetic structure remains a major challenge in population biology (Rundle and Nosil, 2005;Crispo et al, 2006;Nosil and Crespi, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation